“HOW MUCH INDONESIAN CAN I USE?” EXPLORING PRE-SERVICE TEACHERS’ TRANSLANGUAGING EXPERIENCE IN EFL CLASSROOMS - Annisa Rahmadani; Susan Santika; Nida Mujahidah Fathimah; Siti Nurhasanah; RTS Alfira Khairunnisa (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
Translanguaging has received growing attention in multilingual EFL contexts, yet little is known about how pre-service teachers enact this pedagogy after formal exposure in university coursework. This study examined how pre-service EFL teachers enacted translanguaging during teaching practicum and what factors shaped their pedagogical decisions. Drawing on six pre-service English teachers from a public university in Indonesia, the study traced participants’ practicum enactment following a Speaking for Academic Purposes course that introduced translanguaging principles through pedagogical modelling and guided reflection. Data were generated through semi-structured interviews (approximately 15-30 minutes each; ≈100 minutes in total) and analyzed using reflexive thematic analysis (Braun & Clarke, 2023). Findings indicate that translanguaging serves cognitive functions; scaffolding comprehension through planned movement between English and Indonesian and guiding learners back to English for academic expression, affective functions; reducing anxiety, boosting confidence, and supporting participation, and identity-related functions; affirming students’ linguistic repertoires, including local languages, to foster inclusive classroom spaces. However, translanguaging enactment was negotiated within the confines of institutional English-medium expectations, mentor influence, and concerns about balancing English exposure with strategic L1 use. The findings inform EFL teacher education by highlighting the need for explicit, practicum-oriented translanguaging preparation, mentor development that validates principled multilingual pedagogy, and clearer EMI guidance that legitimizes strategic translanguaging in multilingual classrooms.